(untitled) (Medical Forum Monthly, 2024)
Objective: To examine the preferences about different teaching strategies of dental students in our institute. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Faryal Dental College Lahore from November 2018 to April 2019. Materials and Methods: Total one hundred and twenty undergraduate dental students of both genders were included in this study. A self developed questionnaire was distributed to all the students. Student’s preferences for different teaching methodologies were recorded. Analyze the views and preferences between all the students. Results: There were 70 (58.33%) males while 41.67% were females. 85% students reported that the lectures schedule should be announced in advance. 85% of students preferred morning lectures and 15% students preferred afternoon lectures. 96 (80%) students preferred power point lectures method. Most of the student reported that they should have received lecture handouts and study materials before the session and practical work at the end of session. Conclusion: Majority of students preferred power point presentation of lectures. Teachers should have to take students opinion before starting the course, this activity will be helpful to develop a good teaching environment and would have a positive impact on student performance.